The Influence of Financial Literacy and Lifestyle on the Personal Financial Management of Students at Lembah Dempo University - Nanda Oktadiansyah; Elvera Elvera; Nurlela Nurlela (The Future of Education Journal, 2026)
This study aims to analyze the comprehensive effect of financial literacy and lifestyle choices on the personal financial management of active undergraduate students at Universitas Lembah Dempo during the 2026 academic year. Driven by emerging issues in digital consumerism and the rapid expansion of peer-led lifestyle expectations, managing student allowances has become a critical socioeconomic challenge. The research design implements a quantitative approach with an associative research paradigm. The empirical population targeted includes all active students across various departments, totaling 648 students, from which a representative sample of 87 respondents was drawn using the classic Yamane formula combined with an accidental sampling protocol. Primary empirical data collection was systematically operationalized through digitized multi-item questionnaires scored on a 5-point Likert scale. Analytical processes were fully carried out using descriptive statistical testing, instrument validation procedures, internal consistency reliability diagnostics, and multiple linear regression modeling computed via SPSS version 26. The empirical findings reveal that financial literacy independently exerts a highly significant and positive influence on personal financial management capabilities, yielding a significance level of 0.000 (< 0.05). Concurrently, individual lifestyle attributes show a statistically robust and profound predictive impact on how students structure their financial management routines (sig 0.000 < 0.05). Synthesizing both parameters, the simultaneous F-test validates that financial literacy and lifestyle dynamically predict personal financial management, exhibiting an F-value of 427.120 with an absolute significance of 0.000 (< 0.05). The computed coefficient of determination (R2) of 0.910 indicates that 91.0% of the statistical variance observed in students' personal financial management is robustly explained by these two predictors, leaving a minimal 9.0% attributed to external confounding factors. In conclusion, while both elements are highly relevant, financial literacy acts as the most dominant, critical asset in mitigating fiscal distress and reshaping sustainable student financial behaviors.